Analytical Solution of Buoyancy Force and Effects of an Aligned Magnetic Field on an Unsteady MHD Free Convection Flow Oscillating between Two Inclined Plates - Mohan, S. Rama; Maheshbabu, N.; Rao, M. Eswara; Reddy, L. Ramamohan; Ramana, B. (Discontinuity, Nonlinearity, and Complexity, 2026)
This study explores the analytical solution for magneto-hydrodynamic (MHD) free convection flow in an unsteady state occurring between two inclined plates. It takes into account factors such as buoyancy forces, an aligned magnetic field, thermal radiation, chemical reactions, and radiation absorption. By implementing the Analytical Perturbation Method, the analysis yields expressions for velocity, temperature, and concentration profiles, highlighting the interactions among magnetic fields, gravitational forces, and thermal radiation. The findings illustrate notable impacts on flow characteristics and thermal behavior, which is subsequently examined through graphical representations. Additionally, calculations yield tabulated data on heat transfer rates (Nusselt number) and mass transfer rates (Sherwood number).